Benefits and Costs of Legal Policy for the Food Estate Program in Indonesia - Redi, Ahmad; Mizuno, Kosuke (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2025)
To ensure food availability across Indonesia and mitigate potential food crises, the government introduced the Food Estate program under Presidential Regulation No. 109 of 2020. This initiative aims to strengthen national food security through the effective management of food reserves. This study analyzes the legal aspects of the Food Estate concept in Indonesia using a normative juridical approach, which includes a literature review, analysis of relevant laws and regulations, and an examination of legal cases related to the Food Estate program.The findings indicate that the legal framework governing the Food Estate program has undergone several revisions, beginning with Minister of Environment and Forestry Regulation No. 24 of 2020 and later amended by Minister of Environment and Forestry Regulation No. 7 of 2021. The Food Estate program presents both benefits and challenges. While it enhances food security, attracts investment, and increases farmers’ incomes, it also poses risks such as land conflicts, environmental degradation, deforestation, and shifts in agricultural practices that may threaten food sovereignty. Additionally, concerns arise regarding land conversion and the potential for price manipulation by financial stakeholders.